2015
DOI: 10.1038/cddis.2015.144
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 suppresses tumor metastasis by inhibiting macrophage M2 polarization through blockade of efferocytosis

Abstract: Efficient clearance of apoptotic cells (efferocytosis) can profoundly influence tumor-specific immunity. Tumor-associated macrophages are M2-polarized macrophages that promote key processes in tumor progression. Efferocytosis stimulates M2 macrophage polarization and contributes to cancer metastasis, but the signaling mechanism underlying this process is unclear. Intercellular cell adhesion molecule-1 (ICAM-1) is a transmembrane glycoprotein member of the immunoglobulin superfamily, which has been implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 61 publications
(76 reference statements)
0
81
1
2
Order By: Relevance
“…As the incidence and outcomes from atherosclerotic vascular disease differ in males and females, and studies show that estrogen receptor may modulate MR regulation of ICAM-1 in endothelial cells [47], future studies are needed to explore whether this mechanism contributes to plaque formation in females. Another limitation stems from the lack of investigation of macrophages ICAM-1 expression in response to ALDO, which could also contribute to explain the pro-atherogenic effects of ALDO [48]. In fact, MR is expressed in macrophages and affects their M1/M2 polarization and cardiac infiltration [4951].…”
Section: Discussionmentioning
confidence: 99%
“…As the incidence and outcomes from atherosclerotic vascular disease differ in males and females, and studies show that estrogen receptor may modulate MR regulation of ICAM-1 in endothelial cells [47], future studies are needed to explore whether this mechanism contributes to plaque formation in females. Another limitation stems from the lack of investigation of macrophages ICAM-1 expression in response to ALDO, which could also contribute to explain the pro-atherogenic effects of ALDO [48]. In fact, MR is expressed in macrophages and affects their M1/M2 polarization and cardiac infiltration [4951].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of Stat3 by efferocytosis mediates the M2-like polarization of bone marrow macrophages (12). In vivo studies in breast and colon cancer showed that efferocytosis induced M2 polarization and metastasis, while increased cell death correlated with poorer outcomes (13,48). Moreover, the proinflammatory cytokine IL-6 induced M2-like macrophage polarization in human macrophages (49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the potential role of ICAM-1 in cancer metastasis. Clinical research on colorectal cancer has revealed a positive relation between liver metastasis and the sinusoidal expression of ICAM-1 (21); however, a recent study showed that ICAM-1 deficiency in mice accelerated liver metastasis of SL4 colon cancer cells (22). Further studies are needed to determine the role of ICAM-1 in liver metastasis under condition of alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%